2016
DOI: 10.1160/th16-03-0248
|View full text |Cite
|
Sign up to set email alerts
|

Association between anti-apolipoprotein A-1 antibodies and cardiovascular disease in the general population

Abstract: We aimed to determine the association between autoantibodies against apolipoprotein A-1 (anti-apoA-1 IgG) and prevalent cardiovascular (CV) disease (CVD) as well as markers of CV risk in the general population. Cross-sectional data were obtained from 6649 subjects (age 52.6 ± 10.7 years, 47.4 % male) of the population-based CoLaus study. CVD was defined as myocardial infarction, angina pectoris, percutaneous revascularisation or bypass grafting for ischaemic heart disease stroke or transient ischaemic attack, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
31
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 42 publications
(65 reference statements)
7
31
2
Order By: Relevance
“…Our results extend previous findings (19, 22, 25, 26) and suggest that preclinical autoimmunity against apoA-1/HDL—which affects up to one-fifth of the general population—may identify individuals at increased risk of death. Our findings raise the possibility that presence of anti-apoA-1 IgG leads to pathophysiological events affecting not only CV prognosis, but also survival in the long term.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our results extend previous findings (19, 22, 25, 26) and suggest that preclinical autoimmunity against apoA-1/HDL—which affects up to one-fifth of the general population—may identify individuals at increased risk of death. Our findings raise the possibility that presence of anti-apoA-1 IgG leads to pathophysiological events affecting not only CV prognosis, but also survival in the long term.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, similar to what has been reported with other autoantibodies (7), our group recently demonstrated that elevated anti-apoA-1 IgG levels were present in up to 20% of individuals in the general population and associated with prevalent CVD independently of traditional CV risk factors (25). Nevertheless, the association of anti-apoA-1 IgG with all-cause mortality in the general population has not yet been studied.…”
Section: Introductionsupporting
confidence: 82%
See 3 more Smart Citations